LOAD OPTIMIZATION ALGORITHMS FOR INTEGRATION OF DISTRIBUTED GENERATORS IN MAIN ELECTRICAL NETWORKS (Academia Science Repository, 2023)
This paper introduces a hybrid approach to find the optimal location and size of distributed generations (DG) in the radial distribution network (RDN). The proposed approach is based on the whale optimization algorithm (WOA) technique to calculate the optimal allocation of DGs and loss sensitivity index (LSI) to obtain the best buses for DGs installation in RDN. The presented approach is applied to the standard 33- bus RDN to minimize power losses. The results obtained prove that the developed approach can be highly effective in integrating DG into RDN in comparison with other methods in the literature.